Freedom From Seizures Might Be Key to Continuing Occupation After Epilepsy Surgery - Nozaki, Toshiki; Fujimoto, Ayataka; Yamazoe, Tomohiro; Niimi, Keiko; Baba, Shimpei; Yamamoto, Takamichi; Sato, Keishiro; Enoki, Hideo; Okanishi, Tohru (Frontiers in Neurology, 2021)
Introduction: We hypothesized that epilepsy surgery for adult patients with temporal lobe epilepsy (TLE) who obtained freedom from seizures could provide opportunities for these patients to continue their occupation, and investigated continuity of occupation to test this postulation. Methods: Data were obtained from patients who had undergone resective surgery for medically intractable TLE between October 2009 and April 2019 in our hospital. Inclusion criteria were as follows: 1) 16 years old at surgery; 2) postoperative follow-up 12 months; 3) seizure-free period 12 months. As a primary outcome, we evaluated employment status before and after surgery, classified into 3 categories as follows: Level 0, no job; Level 1, students or homemakers (financially supported by a family member); and Level 2, working. Neuropsychological status was also evaluated as a secondary outcome. Results: Fifty-one (87.9%) of the 58 enrolled TLE patients who obtained freedom from seizures after surgery continued working as before or obtained a new job (employment status: Level 2). A significant difference in employment status was identified between before and after surgery (p = 0.007; Wilcoxon signed-rank test). Twenty-eight patients (48.3%) were evaluated for neuropsychological status both before and after surgery. Significant differences in Wechsler Adult Intelligence Scale-III scores were identified between before and after surgery (p < 0.05 each; paired t test). Conclusion: Seizure freedom could be a factor that facilitates job continuity, although additional data are needed to confirm that possibility. Further investigation of job continuity after epilepsy surgery warrants an international, multicenter study.